2014
DOI: 10.1042/bst20140003
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase I (Glo1) and its metabolites in vascular disease

Abstract: Glo1 (glyxoalase I) is a cytosolic protein expressed in all mammalian cells. Its physiological function is the detoxification of MG (methylglyoxal), which is a potent precursor of AGEs (advanced glycation end-products). Although the impact of AGEs on different forms of vascular diseases has been intensively investigated, the evidence for the involvement of Glo1 and MG is still scarce. Recently, several studies have provided significant evidence for Glo1 having a protective effect on microvascular complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Immunohistochemical analyses of the aortic wall by an anatomopathologist showed that the main CCL18-producing cells are macrophages, with a few endothelial cells and fibroblasts. CCL18 is chemotactic for T and B cells (20), is detected in atherosclerosis plaques in regions rich in macrophages (21) and was also reported as a fibro-inflammatory mediator able to stimulate collagen production by lung and dermal fibroblasts (22). In this study, the plasma levels of CCL18 were significantly higher in the AAA population compared with healthy individuals, with the highest concentrations being measured in A+ patients.…”
Section: Discussionsupporting
confidence: 52%
“…Immunohistochemical analyses of the aortic wall by an anatomopathologist showed that the main CCL18-producing cells are macrophages, with a few endothelial cells and fibroblasts. CCL18 is chemotactic for T and B cells (20), is detected in atherosclerosis plaques in regions rich in macrophages (21) and was also reported as a fibro-inflammatory mediator able to stimulate collagen production by lung and dermal fibroblasts (22). In this study, the plasma levels of CCL18 were significantly higher in the AAA population compared with healthy individuals, with the highest concentrations being measured in A+ patients.…”
Section: Discussionsupporting
confidence: 52%
“…Glo1, the ubiquitous key enzyme in the detoxification of α-oxoaldehydes, including MG, is emerging as another major downstream target by which Nrf2 exerts its cytoprotective stress response functions [29] . Indeed, transcriptional control of Glo1 by Nrf2 provides a stress-responsive defense against MG-mediated glycative and oxidative stress, which has been implicated in the pathophysiology of various cellular dysfunctions and diseases, including brain microvascular endothelial barrier dysfunction and vascular diseases [46] , [47] , [48] . Specifically, there is clear evidence that MG accumulation at supra-physiological levels causes chemical modifications of proteins, nucleic acids and lipids [31] , and intensifies the mitochondrial production of ROS [58] , [101] , ultimately exposing cells to glycative and oxidative stress and consequent pleiotropic effects, including cellular dysfunctions, DNA damage and apoptosis [42] , [58] , [59] .…”
Section: Discussionmentioning
confidence: 99%
“…These apparently divergent functions imply that MG, like other reactive species, may exert different or even opposite biological effects, depending on its levels and the cellular context. Interestingly, Glo1 and MG-derived AGEs have been shown to play major and complex roles in vascular physiology and pathophysiology, including the pathogenesis of brain microvascular endothelial barrier dysfunctions [46] , [47] , [48] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the function of Glo1 in macrovascular disease, particularly atherosclerosis, still remains uncertain [ 6 ]. While large epidemiologic studies have not been able to detect effects of different SNPs of the Glo1 gene on formation of atherosclerosis [ 12 , 13 ], Hanssen et al reported higher levels of advanced glycation end products in human carotid atherosclerotic plaques associated with a higher risk of plaque rupture [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…As recently reviewed by us [ 6 ], there is increasing evidence that the balance between production of MG and its detoxification by Glo1 might be involved in the formation and progression of atherosclerotic lesions. In addition, chemical inhibition of Glo1 has been shown to induce atherosclerosis in ApoE deficient mice [ 7 ].…”
Section: Introductionmentioning
confidence: 99%